Дослідження та аналіз конструкторів ботів для месенджерів - Єсін, К. В. (ХНУРЕ, 2023)
This work is devoted to exploring the role of chatbots and bot builders for messengers in the modem world. A chatbot is a special application that allows interaction with third-party services through a chat interface. Messenger bot builders allow creating and configuring chatbots without programming. This tool enables creating bots with various functions, including answering questions, conducting surveys, processing orders, and more. By 2023, over 70% of businesses had already used chatbots or planned to implement them in the coming months. Many Chat and Chatfuel are leaders in the bot builder market, occupying over 60% of the market share, but there are also several other popular bot builders, such as Tars, Landbot, Botsify, and many others